Ecosystem engineering by the wetland plant palmiet: does it control fluvial form and promote diffuse flow in steep-sided valleys of the Cape Fold Mountains - Barclay, Amy (Rhodes University, Faculty of Science, Department of Geography, 2017)
Ecosystem engineering refers to the way that organisms control the structure and function of ecosystems. It has been suggested that palmiet (Prionium serratum, Thurniaceae) works as an ecosystem engineer, shaping peat wetlands in South Africa. However, there is currently a paucity of evidence supporting this claim. Palmiet has a dense root, rhizome and stem system that forms dense stands, growing from channel banks into fast flowing river channels. This slows river flows, traps sediment, which builds up riverbeds and ultimately blocks river channels, turning the river into a wetland. The aim of this study was to determine if palmiet is an ecosystem engineer and to document its pattern of colonisation and the nature of its control of a fluvial system. This was achieved by undertaking vegetation surveys in the Kromrivier Wetland in the Eastern Cape. The data was analyzed using vegetation classification and ordination, where vegetation communities were linked to environmental factors. It was found that palmiet occupied three distinctive habitats; 1) on near-horizontal valley- bottom habitats filled with sediments that are a mixture of autochthonous organic sediment and allochthonous clastic fines, 2) the bed of gullies that have recently filled with coarse grained clastic sediment, and 3) open water bodies. Three conceptual models were developed, one that accounts for the process of gully bed colonisation, sediment trapping and gully filling, another involving rapid colonisation of sedimentary fill from tributary sediment sources that block a gully, and the third involving colonisation of open-water areas that form in former gullies upstream of the blockage. The study suggests that the wetland has been characterised by repeated cutting and filling cycles, despite which, palmiet has repeatedly reinstated diffuse flow conditions across the valley floor. Palmiet was indicated to exert a key control on fluvial form and dynamics of the wetlands in the Kromrivier valley.
Keywords: Prionium serratum; Wetlands -- South Africa -- Eastern Cape; Aquatic plants -- South Africa -- Eastern Cape; Peatland ecology -- South Africa -- Eastern Cape; Kromme River (Eastern Cape, -- South Africa)